2002
DOI: 10.1152/nips.01369.2001
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1: Physiological and Pathophysiological Roles

Abstract: Plasminogen activator inhibitor 1 (PAI-1) inhibits plasminogen activators (u-PA and t-PA) by forming stable complexes endocytosed via a low-density lipoprotein receptor superfamily member-dependent mechanism. PAI-1 circulates actively in plasma and latently in platelets but is also secreted and deposited into the matrix by several cells, where it participates in tissue repair processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
190
0
23

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(219 citation statements)
references
References 18 publications
6
190
0
23
Order By: Relevance
“…11 PAI-1 is an important downregulator of plasmin activation and is expressed in animals and in cells after exposure to numerous agents, including cytokines and LPS. [22][23][24] In animal models of endotoxemia, antibodymediated inhibition or genetic knockout of PAI-1 significantly attenuated fibrin deposition in tissues, suggesting that PAI-1 activity is important for this effect of LPS exposure. [25][26][27] Interestingly, hepatic expression of the gene encoding PAI-1 is enhanced in LPS/RAN-treated rats, 10 and this expression is mirrored by an augmented concentration of PAI-1 protein in serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11 PAI-1 is an important downregulator of plasmin activation and is expressed in animals and in cells after exposure to numerous agents, including cytokines and LPS. [22][23][24] In animal models of endotoxemia, antibodymediated inhibition or genetic knockout of PAI-1 significantly attenuated fibrin deposition in tissues, suggesting that PAI-1 activity is important for this effect of LPS exposure. [25][26][27] Interestingly, hepatic expression of the gene encoding PAI-1 is enhanced in LPS/RAN-treated rats, 10 and this expression is mirrored by an augmented concentration of PAI-1 protein in serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Early modulation of TF activity is presently a therapeutic strategy in systemic inflammatory response syndrome patients [23]. On the other hand, PAI-1 plays an important role in the regulation of fibrinolysis and proteolysis by inhibiting tissue-type plasminogen activator and urokinase-type plasminogen activator [24]. Studies in animal models have indicated that increased PAI-1 activity enhances thrombosis, and antibodies against PAI-1 prevent the progression of thrombosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of uPAR with uPA, PAI-1, low-density lipoprotein-receptor-related protein (LRP), vitronectin and integrins provides a novel mechanism for cell chemotaxis, adhesion and migration [10].…”
Section: Introductionmentioning
confidence: 99%